Quality of Life and Nutritional Parameters of Celiac Patients in Mar Del Plata, Argentina - Motta, Estela Leonor (2019)
Background: Celiac disease (CD) is one of the most common causes of chronic malabsorption. The changes that occur in the diet due to the influence of gluten free diet (GFD) lead to a lower content in the intake of fiber and vitamins. Some authors point out that the higher cost of GF foods, the lower availability of those in social events, the impaired patient’s quality of life, could influence the degree of adherence to the GFD. Our aims were to evaluate the nutritional status, identifying the factors that are associated with adherence to the gluten-free diet (DLG) and the quality of life of a group of CD patients in Mar del Plata. Methods: CD patients were recruited from outpatient of clinic and gastroenterology unit of Oscar Alende Hospital, Mar del Plata and Argentina Celiac Association and had blood drawn for micronutrients concentration. Quality of life was evaluated by SF12 questionnaire, factors and adherence to GFD were determined by factors questionnaire and the Celiac Dietary Adherence Test (CDAT). Results: 47% of the participants had high adherence to GFD. The large supply of gluten-free foods without options during social events was significantly associated with the worst adherence to GFD. The average concentrations of folic acid, magnesium, iron and vitamin B12 were within the normal ranges; however, 6.7, 7.0 and 33.3% of the low adherent group showed low serum concentrations of iron, vitamin B12 and folate, respectively, while 7.7 and 53.8% of the high adherent exhibited low serum concentrations of iron and folate, respectively. Approximately 14.2% had anemia, only 7.1% had iron deficiency anemia. 54% of patients reported eating corn-based foods 3 or more times per week. The general perception of health was low in the age range between 18 and 40 years (34.3 ± 22.0) and the energy and vitality values were low in the same group (37.5 ± 25.2). Conclusions: Evaluation of quality of life and micronutrients indicate the need to support the patients in their treatment and to increase the supply of GF foods and the supplementation with vitamins and micronutrients of the GFD.